Synthesis, Characterization and Evaluation of Overbased Magnesium Fatty Acids Detergent for Medium Lubricating Oil - A-K Mohammed, Abdul Halim; R. Ahmad, Mohammed; A. K. Al-Messri, Zainab (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
A series of overbased magnesium fatty acids such as caprylate, caprate, laurate, myristate, palmitate, stearate and oleate) were synthesized by the reaction of the fatty acids with active – 60 magnesium oxide and carbon dioxide (CO2) gas at 60 oC in the presence of ammonia solution as catalyst, toluene / ethanol solvent mixture (9:1vol/vol) was added. The prepared detergent additives were characterized by FTIR, 1HNMR and evaluated by blending each additive in various concentrations with medium lubricant oil fraction (60 stock) supplied by Iraqi Midland Refineries Company. The total base number (TBN, mg of KOH/g) was determined, and the results of TBN were treated by using two-way analysis of variance (ANOVA) test. It was found that the number of carbons in the fatty acid (C8-C18) used for overbased detergent preparation had slight effect on the TBN of the oil, while detergent concentrations (1-5% wt/wt) had a significant effect on the TBN of the blended oil. The oxidation stability of the oil blends with 2% of overbased magnesium palmitate and overbased magnesium stearate detergents was evaluated, and the results showed that these blends gave higher oxidation stability compared with the blends with standard antioxidant supplied by Midland Refineries Company.